Renewable Energy Development and Its Contribution to Sustainable Economic Growth in Kazakhstan - Turlybekova, Altynay; Agabekova, Gulzhan; Sadykov, Aripkhan; Sergaziyeva, Madina; Keneshbayev, Bektur; Kelesbayev, Dinmukhamed (International Journal of Energy Economics and Policy, 2025)
This study aims to analyze the relationship between the development of renewable energy sources and sustainable economic growth in Kazakhstan for the period 2000-2024. The study used official national statistical data: gross domestic product (GDP, by production method), labor productivity indices, GDP energy intensity, inflation dynamics, and renewable energy production capacities. In addition, the oil and gas sector, which is the traditional basis of the economy, was considered as a control variable. Methodologically, descriptive statistical analysis, correlation estimation, and econometric models were used. In particular, the autoregressive distributed lag (ARDL) method and the Granger causality test were used to identify short- and long-term relationships. Labor productivity, energy intensity, inflation, and oil and gas sector indicators were included in the econometric model as explanatory variables. Preliminary results show that the development of renewable energy sources has a positive impact on both GDP growth and labor productivity. At the same time, it was found that reducing energy intensity leads to increased economic efficiency. However, it was noted that inflationary volatility and dependence on the oil market limit the volume and sustainability of investments in renewable energy. The results of the Granger causality test revealed that renewable energy production contributes to economic growth. This study is one of the first empirical works to comprehensively analyze the development of renewable energy sources in Kazakhstan in the context of economic diversification. The results have important practical significance in achieving the UN Sustainable Development Goals, in particular SDG-7 (Affordable and Clean Energy) and SDG-8 (Sustainable Economic Growth and Productive Work). Recommendations include strengthening institutional support, increasing investments in renewable energy, and integrating energy efficiency policies into national development strategies.